Análise ergonômica do ambiente de trabalho para operadores de tratores e colhedoras agrícolas - Rossi, Marco Antônio [UNESP] (2007)
The introduction of new technologies in plantation fields, such as the use of tractors machines for agricultural activities, brought some problems to operators. The purpose of this research is to analyze the tractors and harvesters agricultural operator s working place in order to avoid security and health problems that the use of new technologies may bring to them. For this research, eight tractors and two harvesters agricultural with average power of 66kw were used. All ten agricultural machines belong to the Universidade Estadual Paulista, city of Botucatu, State of São Paulo, Brazil. The existing literature regarding to the diversity in ergonomics and agricultural tractors and harvesters was analyzed and discussed. Together with the ergonometry technical parameters and agricultural tractors and harvesters machines themselves, other researches were required such as those related to anthropometry, interface systems - information and action, human tiredness, noise, comfort - seats and conformities, biomechanics - control and handling, working environment and technology. At first, a demand analysis methodology was used by applying individual questionnaires to the operators of the agricultural machines in order to collect information, such as muscular and mental tiredness. The result of the demand analysis revealed the problem, and therefore, the need to apply an Ergonomic Analysis of the Work (AET) by using four approaches of this methodology. The approaches were: anthropometry, biomechanics, comfort and noise. In anthropometry, the method was applied by comparing the anthropometric measures to the measures of eight of the agricultural tractors machine 4 operators and two harvesters. In biomechanics the measures of control and handling location regarding two tractors and one harvester agricultural were taken, in that case, it was necessary a scientific method based on the existing... (Complete abstract click electronic access below)